Pengaruh Pendidikan Kesehatan Tentang Metode Fast Terhadap Pengetahuan Keluarga Yang Menderita Hipertensi Di Desa Passo Kecamatan Baguala - Maritje S.J. Malisngorar; Vero Anggi Junike Samloy; Mariyati Mardjuky; Rini Hatma Rusli (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Background: Hypertension is one of the most common cardiovascular diseases and affects many people. Hypertension is a major health problem not only in Indonesia but also throughout the world, this is because hypertension is one of the entry points or risk factors for diseases such as heart disease, kidney failure and stroke which makes this disease the number one cause of death in the world every year. FAST is an acronym for Facial movement, Arm movement, Speech, and Time to call which can be used to identify and detect the occurrence of a stroke. Early detection of stroke with FAST is effective in speeding up intervention thereby minimizing disability. This method can be taught to patients and families because the family is the person closest to the patient or individual at high risk, as well as an effort to empower the family in recognizing the signs and symptoms of a stroke early in the prehospital setting. Objective: To determine the effect of health education about the FAST method on the knowledge of families suffering from hypertension in Passo Village, Baguala Subdistrict. Method: This research uses quantitative research methods with a pre-experimental research type with the design used being a one group pre test-post test design. The sample consisted of 25 respondents with a total sampling approach, instruments in the form of questionnaires and leaflets, data analysis using the Wilcoxon. Results: Respondents' knowledge decreased by 0, knowledge remained 0, knowledge increased by 25 (p-value = 0.000). Conclusion: There is an influence of health education about the FAST method on the knowledge of families suffering from hypertension in Passo Village, Baguala Subdistrict.